Purification of bacterial membrane sensor kinases and biophysical methods for determination of their ligand and inhibitor interactions - Hussain, Rohanah; Harding, Stephen E.; Hughes, Charlotte S.; Ma, Pikyee; Patching, Simon G.; Edara, Shalini; Siligardi, Giuliano; Henderson, Peter J.F.; Phillips-Jones, Mary K. (Portland Press, 2016)
This article reviews current methods for the reliable heterologous overexpression in Escherichia coli and purification of milligram quantities of bacterial membrane sensor kinase (MSK) proteins belonging to the two-component signal transduction family of integral membrane proteins. Many of these methods were developed at Leeds alongside Professor Steve Baldwin to whom this review is dedicated. It also reviews two biophysical methods that we have adapted successfully for studies of purified MSKs and other membrane proteins–synchrotron radiation circular dichroism (SRCD) spectroscopy and analytical ultracentrifugation (AUC), both of which are non-immobilization and matrix-free methods that require no labelling strategies. Other techniques such as isothermal titration calorimetry (ITC) also share these features but generally require high concentrations of material. In common with many other biophysical techniques, both of these biophysical methods provide information regarding membrane protein conformation, oligomerization state and ligand binding, but they possess the additional advantage of providing direct assessments of whether ligand binding interactions are accompanied by conformational changes. Therefore, both methods provide a powerful means by which to identify and characterize inhibitor binding and any associated protein conformational changes, thereby contributing valuable information for future drug intervention strategies directed towards bacterial MSKs.